Kajian Numerik Pengembangan Symmetrical Blade Propeller Untuk Kapal Patroli 60m dengan Menggunakan Teori Lifting Line - Mahendra Indiaryanto; I Made Ariana (Universitas Muhammadiyah Sidoarjo, 2017)
The development of technology science in the field of maritime is one aspect that needs to be considered. One of them is the development of a propulsion system that is able to work efficiently (Aspects of hydrodynamics) On patrol boats of Indonesian waters guard. Because during this design and manufacture of propellers in need on fast boats is highly dependent on foreign parties. Therefore, the purpose of this study was to produce a propulsion system design suitable with a 60m patrol boat. So that it can be standardized the main size of the boat with its propulsion system. This research is conducted through several stages, where we design the propulsion system and calculated numerically computation (Matlab) Which will be used as a performance analysis of the design that has been determined. So from the results it is known, that the type of propeller boat type 60m patrol match with the engine of the ship that has been set.